Seasonal evaluations of urinary androgen metabolites and semen quality in domestic long-tailed chinchilla (Chinchilla lanigera) under natural photoperiod - Dominchin, Maria Florencia (2014)
Chinchilla spp. is a South American hystricomorph rodent genus currently considered almost extinct in the wild. The high quality of chinchilla fur motivated the harvesting of chinchillas for the fur market. Reproductive biology advances come from studies on commercially exploited animals, especially Chinchilla lanigera. We studied seasonal variation of urinary androgen metabolites, sperm concentration and sperm functional activity in males of domestic Chinchilla lanigera under natural photoperiod. In Córdoba city (31° S-64° W; Argentina), within the same latitudes as those of the historic Andean distribution (tropical deserts; 15°-34° S), domestic males (n= 7) were studied in May (autumn), August (winter), November (spring), and February (summer). Urine was seasonally collected (over 24. h; once for season, 4 in total) to measure urinary androgen metabolites (RIA), before semen collection by electroejaculation. The results indicated that although testicular volume (relative to body weight) and values of sperm functional activity did not show seasonal changes, a seasonal variation in androgen excretion was detected, with the highest values occurring during "short" light/dark cycles (autumn-winter). In addition, viable spermatozoa with intact acrosome mean values during winter-spring were higher than in autumn or summer. This study provides information that might contribute to the assessment of testicular activity in male chinchilla subjected to genetic selection in the fur industry. In addition, since domestic chinchilla still share some genomic characteristics with their counterparts in the wild, results presented may alsocontribute to ex situ breeding program of endangered chinchilla. In conclusion, natural photoperiod cycle affects testicular activity in domestic chinchilla.